2016
DOI: 10.1093/ecco-jcc/jjw104
|View full text |Cite
|
Sign up to set email alerts
|

The Ulcerative Colitis Endoscopic Index of Severity is Useful to Predict Medium- to Long-Term Prognosis in Ulcerative Colitis Patients with Clinical Remission

Abstract: The UCEIS is useful to predict the medium- to long-term outcomes of UC patients with clinical remission. The absence of bleeding or mucosal damage is important for maintaining clinical remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…In a prospective study of 187 patients with endoscopic remission (Mayo sub‐score 0 or 1), 9% with Mayo sub‐score 0 relapsed during the first 6 months of follow‐up, compared to 37% with Mayo endoscopic sub‐score 1 ( P < 0.001) . Interestingly, preliminary work from Japan suggests that the UCEIS (0 vs. 1 or 2) may be able to discriminate outcomes over 2 years in those with a Mayo endoscopic sub‐score 0 . Among 84 patients with a Mayo Clinic endoscopy sub‐score of 0, 19/20 (95%) of those with a UCEIS of 0 remained in remission for 23 months, compared to 48/64 (77%) with a UCEIS of 1 or 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective study of 187 patients with endoscopic remission (Mayo sub‐score 0 or 1), 9% with Mayo sub‐score 0 relapsed during the first 6 months of follow‐up, compared to 37% with Mayo endoscopic sub‐score 1 ( P < 0.001) . Interestingly, preliminary work from Japan suggests that the UCEIS (0 vs. 1 or 2) may be able to discriminate outcomes over 2 years in those with a Mayo endoscopic sub‐score 0 . Among 84 patients with a Mayo Clinic endoscopy sub‐score of 0, 19/20 (95%) of those with a UCEIS of 0 remained in remission for 23 months, compared to 48/64 (77%) with a UCEIS of 1 or 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, preliminary work from Japan suggests that the UCEIS (0 vs. 1 or 2) may be able to discriminate outcomes over 2 years in those with a Mayo endoscopic sub‐score 0 . Among 84 patients with a Mayo Clinic endoscopy sub‐score of 0, 19/20 (95%) of those with a UCEIS of 0 remained in remission for 23 months, compared to 48/64 (77%) with a UCEIS of 1 or 2 . Furthermore, in the referral centre UC cohort in Nancy, France, in 55 patients with a Mayo endoscopic sub‐score of 0 or 1, 8/55 (15%) came to colectomy during a median follow‐up of 48 months, all with a Mayo endoscopic sub‐score of 1 at first evaluation .…”
Section: Discussionmentioning
confidence: 99%
“…According to our best knowledge this is one of the first studies to assess the correlation between the Lichtiger Index and the UCEIS. In a recent study of Arai et al [22] the UCEIS demonstrated good correlation with the pMayo score (r=0.637), it was also correlated with the Lichtiger index but the data were not shown in the article.…”
Section: Discussionmentioning
confidence: 80%
“…The percentages of complete mucosal healing in the twice-daily budesonide foam group were 46.4 % compared to 23.6 % in the once-daily group or 5.6 % in the placebo group [57]. Because complete endoscopic remission contributes to the long-term clinical outcomes in patients with UC [58], budesonide foam can be used prior to other topical therapies to achieve endoscopic remission in distal UC patients.…”
Section: Budesonide Foammentioning
confidence: 98%